Brief Report: Impact of COVID-19 on Cabotegravir Plus Rilpivirine Long-Acting Dosing Across 6 Ongoing Global Phase IIb and III Clinical Trials. (1st October 2022) - Czarnogorski, Maggie; Benn, Paul; McCoig, Cindy; Nwafor, Toyin; Griffith, Sandy; Sutton, Ken; Harrington, Conn; Saggu, Parminder; Yague, Itziar; Williams, Will; Español, Carlos M.; Goodchild, Jessica; et al.
Abstract : Background: Cabotegravir + rilpivirine long-acting (LA) is a novel antiretroviral therapy (ART) administered intramuscularly monthly or every 2 months by a health care provider. The COVID-19 pandemic presents a potential challenge to patients' ability to attend scheduled clinic visits for dosing administration. Setting: This analysis evaluated implementation fidelity across 6 phase IIb/III/IIIb cabotegravir + rilpivirine LA clinical trials in 16 countries during the COVID-19 pandemic. Methods: COVID-19-impacted visits were defined as modified dosing visits for which oral therapy was provided to participants unable to attend the clinic or injection visits that were rescheduled. Data from December 1, 2019, to March 1, 2021, were aggregated and analyzed using descriptive statistics. Results: Of 2127 participants in cabotegravir + rilpivirine LA trials, 1997 (94%) had LA dosing visits proceed as planned during the COVID-19 pandemic. Of 130 (6%) participants with injection visits affected by COVID-19, most were from North America (57%) and Europe (26%). Most participants with COVID-19-impacted visits used oral therapy with cabotegravir + rilpivirine (75%) or alternative oral standard-of-care ART (21%) to maintain continuous ART. The most common reasons for missed visits were clinic closure/staffing constraints (48%) and COVID-19-related travel restrictions (23%). Most (98%) participants who used oral ART maintained virologic suppression; 2 participants had viral load between 50 and 100 copies/mL. Conclusion: During the COVID-19 pandemic, most trial participants maintained their LA dosing schedules. Flexibility of the LA dosing regimen, with the ability to switch to oral therapy, facilitated continuous ART provision and implementation fidelity.